Nanocristais coloidais como emissores de luz em microcavidades semicondutoras - Carlos Gabriel Pankiewicz (2015)
Pure quantum phenomena are the basis of the operation of several nanostructured semicon- ductor devices. Among them, the Purcell Effect is related to the control of the spontaneous emission of a given physical system. The comprehension of such effects is vital for the study of cavity quantum electrodynamics, a theory that describes how a semiconductor microcavity interacts with a light emitter. A semiconductor microcavity can be viewed as a symmetry break on an otherwise periodic refraction index distribution. When illuminated by a coherent light source, only a few speci c wavelengths are re ected by the system, the so called electromagnetic modes. For a complete mapping of the cavity modes a light emitter should be positioned in their surroundings and the emitted light should be comprised by wavelengths in the same spectral region as the cavity modes. Topics related to those effects are discussed in this thesis and the main theme is the study of the interaction between colloidal nanocrystals and a two-dimensional photonic crystal with a double-waveguide heterostructure. Firstly, a complete optical characterization of the double heterostructure microcavity th- rough drop-cast CdTe/CdS and CdSe/CdS nanocrystals was performed. No control of the exact spatial positions of these nanoparticles was achieved, initially. Through this procedure the electromagnetic modes of each microcavity within our sample were mapped by photolumi- nescence measurements. Besides good agreement between our results and previous works in the literature, done with different light-sources, a more thorough method of deposition was needed to obtain higher quality fators. Simulations via FDTD (Finite-Difference Time-Domain) and GME (Guided Mode Expan- sion) were carried out to optimize structural parameters before sample fabrication and to help understanding some of the experimental results. To predict with accuracy the energies of these systems' electromagnetic modes an eigenvalue equation, coming from the decoupling of the Maxwell'; s equation, must be solved applying one of these methods. Besides that, the electric eld pro le inside the microcavity can be known. To determine where exactly is the electric eld maximum is paramount for spatial-tunning cavity and emitter. Site-control nanocrystals deposition on top of the double heterostructure microcavities was achieved throug an atomic force microscope (AFM) based technique. Less variation in the system's refractive index distribution was achieved in this way in an effort to increase strong coupling effects between the cavity and the light emitter. The higher the spatial and spectral sintony between the two the higher the probability of a full control of the spontaneous emission inside the device. CdTe/CdS nanocrystals emission dynamics and particle laser-induced degradation were in- vestigated in order to identify if the nanoclusters deposited with the AFM were capable of emitting light intense enough to allow the observation of the interesting quantum phenomena aforementioned. Signi cant spectral shift and intensity decrease were observed in the collec- ted emission spectra, suggesting that light emitted by a small cluster of nanoparticles could be highly affected by the laser excitation intensity and such effects should be regarded when devices such as those presented in this thesis are tailored.